Kits of information to knowledge / Fatin Nurain Baharuddin and Nor Farhanah Shahroom - Baharuddin, Fatin Nurain; Shahroom, Nor Farhanah (Faculty of Information Management, 2015)
Tools to knowledge discussed about the tools that been used in order to access and retrieve knowledge. The article starts with describing slightly the meaning of knowledge itself. It then moved to the value of knowledge as intellectual property and the needs of respecting the creator of the information, since the information that person gain can transform a person to become knowledgeable. Thus, it is important to cite or acknowledge the creator of resources that been used. In defining the information sources, it involved three stages which are primary sources, secondary sources and tertiary sources. This information sources represent the way of people create and distribute information in intention of making it as knowledge. The main highlight in this article start with the old version of retrieval tools in library circumstances which are book catalogue, card catalogue and Computer Output Machine Catalogue (COM). After decades, the old version has been substitute by new sophisticated technologies which is more modern, effective and efficient. The technologies that library served are Online Public Access Catalog (OPAC), online database and internet with their pros and cons.